The Algorithmic Precarity of 'Ojol' Drivers: Investigating the Gig Economy and Digital Resistance in Southeast Asia’s Largest Market - Wiratama, La Ode; Lamaddukelleng, Sultan Rasyid; Putri, Zahwa Mahira (Universitas Negeri Semarang, 2025)
The rise of ride-hailing platforms like Gojek and Grab has transformed Indonesia into one of the world’s largest laboratories for the gig economy. However, beneath the promise of